2006
DOI: 10.1128/aem.02988-05
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Biocolloid Collision Efficiencies for Granular Activated Carbon by Use of a Two-Layer Filtration Model

Abstract: Point-of-use filters containing granular activated carbon (GAC) are an effective method for removing certain chemicals from water, but their ability to remove bacteria and viruses has been relatively untested. Collision efficiencies (␣) were determined using clean-bed filtration theory for two bacteria (Raoutella terrigena 33257 and Escherichia coli 25922), a bacteriophage (MS2), and latex microspheres for four GAC samples. These GAC samples had particle size distributions that were bimodal, but only a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…Presumably, when they were injected together, the less negatively charged gly- coprotein-coated CPMs attached to the more negatively charged unmodified CPMs and were carried along. The ␣ values calculated were Ͼ1 and similar to those found for granular activated carbon (38), showing that the material is very effective at removing colloids. Low ␣ values represent low levels of removal, and conversely, high ␣ values represent high levels of removal.…”
Section: Resultssupporting
confidence: 62%
“…Presumably, when they were injected together, the less negatively charged gly- coprotein-coated CPMs attached to the more negatively charged unmodified CPMs and were carried along. The ␣ values calculated were Ͼ1 and similar to those found for granular activated carbon (38), showing that the material is very effective at removing colloids. Low ␣ values represent low levels of removal, and conversely, high ␣ values represent high levels of removal.…”
Section: Resultssupporting
confidence: 62%
“…In such case, the single collector contact efficiency might be under estimated, giving rise to attachment efficiencies in excess of unity. Others (Shellenberger and Logan, 2002;Morrow et al, 2005;Paramonova et al, 2006;Yang et al, 2006;Lutterodt et al, 2009a) have also reported on attachment efficiencies above 1. For the remaining three strains (2041, 1514, and 2049), it was difficult to find an explanation for their very high attachment efficiencies of 1.42, 1.61 and 2.10, other than to assume that the bacteria size that was used in calculating the single collector contact efficiency had been wrong, most likely due to the presence of surface structures sticking out of the surface of these strains, thereby actually acting as a bigger colloidal particle than used in the TE correlation equation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in some cases, L α values greater than 1 were found. The latter is not very strange (Shellenberger et al, 2002;Morrow et al 2005;Paramonova et al 2006), due to the presence of cell surface organelles like flagella and pili that extend beyond the cell surface. In such case, the aspect ratio used in the computation of the single-collector contact efficiency might be under estimated.…”
Section: Transport Distance Dependent Sticking Efficiency Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For interaction controlled assays, sufficient transport of bacteria toward a collector surface is required. Packed bead reactors constitute such a system and indeed packed bed reactors have been applied in bacterial removal by carbon particles (Paramonova et al, 2006), but reproducible packing of the reactor system is difficult. Moreover, the bacterial fate in terms of growth and reproduction upon adhesion to a carbon particle cannot be determined, as generally only breakthrough curves of bacteria passing the system are measured.…”
Section: Introductionmentioning
confidence: 99%